The Correlation between Position and Duration Use of Laptops with Musculoskeletal Disorders (MSDs) - Tanzila, Raden Ayu; Prameswarie, Thia; Hartanti, Miranti Dwi; Denaneer, Talitha (Universitas Muhammadiyah Yogyakarta, 2021)
The pandemic period forces all learning processes to be carried out online by utilizing internet facilities with a laptop. The position of using a laptop that is not ergonomic can cause musculoskeletal disorder. This study aims to determine the correlation between position and duration of student use of laptops during online learning with Musculoskeletal Disorders (MSDs). This research is analytic observational with a cross-sectional approach. The research was conducted on active students of the Medical Study Program, Muhammadiyah Palembang University, with 416 respondents. Primary data collection was taken using a questionnaire with a Nordic Body Map score. The analysis technique used the Chi-Square test. The results showed that the respondents had a high duration of laptop use (48.8%), with a not good position (42.3%).Most musculoskeletal disorders were felt in the neck (75.5%). There was a correlation between the position of using a laptop and musculoskeletal disorders (p 0.652). However, there was no correlation between the duration of laptop use and musculoskeletal disorders (p 0.002). It can be concluded that the position of using a laptop that is not ergonomic caused musculoskeletal disorders.